ACCOUNTING MEASUREMENT IMPACT OF CHANGES IN PRICE LEVELS ON FINANCIAL STATEMENTS AND FINANCIAL SUPPLY CHAIN ELEMENTS - Murtada Rashid Salih; Mohanad Hamad Obaid; Aqeel Abdulhussen Oudah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
One of the primary objectives of management accounting is to provide users with the information needs and demands to assist in making economic decisions in relation to the business unit. Accounting information, including accounting management, plays an important role in allocating economic resources as a measure of measurement (assumption of monetary stability) and financial. One of the obvious assumptions is the preparation of financial statements for economic activities. In a system based on historical cost, assets and liabilities are measured at the acquisition cost. But with the change in the general level of prices due to economic conditions, such as inflation or stagnation, or change in technology, the value of money also varies accordingly, as a result, the value of the amounts reported in the financial statements is not reliable on the assumption that the money is stable. In public-based accounting, you can compare incomes and expenses in the best way, because the same currency is used. Key Words: Activity-Based Costing, Budget, Governmental Organizations, Operational Budgeting. The purpose of the present research is to create a resource-efficient system integrating resources and providing quick access to the correct information as a competitive advantage for organizations. The purpose of this study was to investigate the effect of implementing the purchasing module of the organization's resource planning system on the performance of supply chain management.